2018
DOI: 10.1186/s13063-018-2792-3
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a group-based computerized HIV/STI prevention intervention for black women who use drugs in the criminal justice system: study protocol for E-WORTH (Empowering African-American Women on the Road to Health), a Hybrid Type 1 randomized controlled trial

Abstract: BackgroundThis paper describes the study protocol of a hybrid type I randomized controlled trial that evaluates the effectiveness and cost-effectiveness of implementing Empowering African-American Women on the Road to Health (E-WORTH), an Afrocentric, group-based, computerized human immunodeficiency virus (HIV)/sexually transmitted infection (STI) prevention intervention for controlled substance-using black women in community corrections settings in New York City.Methods/designWe provide an overview of E-WORTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Four studies (Choo et al, 2016; Humphreys, Tsoh, Kohn, & Gerbert, 2011; Klevens et al, 2012; Klevens, Sadowski, Kee, Garcia, & Lokey, 2015) additionally enhanced the waiting-room screening tools via personalized feedback using written messages or animated avatars (including a cartoon parrot and a video doctor) to encourage victims to speak to their providers during their visit. One study (Littleton, Grills, Kline, Schoemann, & Dodd, 2016) described an online support group for victims of sexual assault, including those assaulted by a current or former intimate partner; other group-involved interventions included women using tablets individually to complete self-paced modules during a group educational session (Gilbert et al, 2015, 2016; Johnson et al, 2018). Solutions to connect health-care providers—specifically mental health-care providers—to current or former victims of IPV included e-mail- and video-delivery of cognitive behavioral therapy (CBT; Gray et al, 2015; Hassija & Gray, 2011; Hesser et al, 2017) or else video-mediated triage into appropriate services (Thomas et al, 2005), particularly for rural IPV victims.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies (Choo et al, 2016; Humphreys, Tsoh, Kohn, & Gerbert, 2011; Klevens et al, 2012; Klevens, Sadowski, Kee, Garcia, & Lokey, 2015) additionally enhanced the waiting-room screening tools via personalized feedback using written messages or animated avatars (including a cartoon parrot and a video doctor) to encourage victims to speak to their providers during their visit. One study (Littleton, Grills, Kline, Schoemann, & Dodd, 2016) described an online support group for victims of sexual assault, including those assaulted by a current or former intimate partner; other group-involved interventions included women using tablets individually to complete self-paced modules during a group educational session (Gilbert et al, 2015, 2016; Johnson et al, 2018). Solutions to connect health-care providers—specifically mental health-care providers—to current or former victims of IPV included e-mail- and video-delivery of cognitive behavioral therapy (CBT; Gray et al, 2015; Hassija & Gray, 2011; Hesser et al, 2017) or else video-mediated triage into appropriate services (Thomas et al, 2005), particularly for rural IPV victims.…”
Section: Resultsmentioning
confidence: 99%
“…We define mHealth as Internet- or technology-mediated approaches to provision of health resources or interventions. Primary intervention through educational tools may be more easily disseminated over the Internet- and web-based media that are already used by target populations (Johnson et al, 2018). Physicians and other providers may have more success identifying individuals in need of IPV prevention services when waiting room screenings are completed on a computer or tablet rather than using a paper form (Klevens et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The timely, actionable findings allowed for a rapid-cycle approach to evaluation in which ongoing feedback was provided to program stakeholders to support learning, adaptation, and continuous quality improvement (Keith et al, 2017). The framework has also been used to study the implementation of substance use treatment programs (Sorensen & Kosten, 2011) and HIV programming for women in community corrections (Johnson et al, 2018). Another study applied the framework to categorize and interpret the processes involved in the adoption of the XR-NTX injection at nine addiction treatment centers contracted with a singular health plan and found that it effectively captured relevant issues related to authorization processes, provider networks, and organizational culture (Alanis-Hirsch et al, 2016).…”
Section: State Targeted Response To the Opioid Crisis (Str) And The Cmentioning
confidence: 99%
“…Using the technology-based platform in DL is a means of achieving a wider audience and thus allowing: i) monitoring quality and ensuring uniformity of the information provided, ii) training entire teams of a local community, iii) reaching a much larger number of participants and iv) increasing capacity of professionals to reduce violence in their communities (Hertz et al, 2008). Some authors suggested that the use of educational tools to primary intervention may be more easily disseminated over the Internet-and web-based media (Johnson et al, 2018). Tarzia and collaborators (2015) have also recognized web-based interventions for survivors of IPV as an alternative to f2f approaches, allowing to overcome some of the barriers that often interfere with the seek for help.…”
Section: Background: Violence and Cyberviolencementioning
confidence: 99%